ddRAD Sequencing-Based Identification of Genomic Boundaries and Permeability in Quercus ilex and Q. suber Hybrids - López de Heredia, Unai; Mora-Márquez, Fernando; Goicoechea, Pablo G.; Guillardín-Calvo, Laura; Simeone, Marco C.; Soto, Álvaro (Frontiers in Plant Science, 2020)
Hybridization and its relevance is a hot topic in ecology and evolutionary biology. Interspecific gene flow may play a key role in species adaptation to environmental change, as well as in the survival of endangered populations. Despite the fact that hybridization is quite common in plants, many hybridizing species, such as Quercus spp., maintain their integrity, while precise determination of genomic boundaries between species remains elusive. Novel high throughput sequencing techniques have opened up new perspectives in the comparative analysis of genomes and in the study of historical and current interspecific gene flow. In this work, we applied ddRADseq technique and developed an ad hoc bioinformatics pipeline for the study of ongoing hybridization between two relevant Mediterranean oaks, Q. ilex and Q. suber. We adopted a local scale approach, analyzing adult hybrids (sensu lato) identified in a mixed stand and their open-pollinated progenies. We have identified up to 9,435 markers across the genome and have estimated individual introgression levels in adults and seedlings. Estimated contribution of Q. suber to the genome is higher, on average, in hybrid progenies than in hybrid adults, suggesting preferential backcrossing with this parental species, maybe followed by selection during juvenile stages against individuals with higher Q. suber genomic contribution. Most discriminating markers seem to be scattered throughout the genome, suggesting that a large number of small genomic regions underlie boundaries between these species. A noticeable proportion of the markers (26%) showed allelic frequencies in adult hybrids very similar to one of the parental species, and very different from the other; a finding that seems relevant for understanding the hybridization process and the occurrence of adaptive introgression. Candidate marker databases developed in this study constitute a valuable resource to design large scale re-sequencing experiments in Mediterranean sclerophyllous oak species and could provide insight in species boundaries and on adaptive introgression between Q. suber and Q. ilex.